(untitled) (Conferencea, 2022)
In the context of the globalization of today’s economy, several promising changes have been made in the higher education system, such as reforms in all sectors of the country. Forming a competitive environment in the field of national training, ensuring effective integration of the higher education, strengthening the material and technical base, education, enterprises and organizations today to formulate educational, scientific and production, today one of the current issues of the day. To compare the financial stability of higher educational institutions, training highly qualified and mature personnel based on the mechanisms, according to the National Training Preparation Program, to find a place in life is to help.